PENGARUH KUALITAS PRODUK TERHADAP MINAT BELI ULANG MELALUI KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING - Nurfalah, Rima Febriyanti; Yulianingsih; Pramestidewi, Chandra Ayu (Fakultas Ekonomi Universitas Djuanda, 2025)
This study is motivated by the increasing competition in the beverage industry, which requires companies to maintain product quality in order to enhance consumer satisfaction and encourage repurchase intention. The purpose of this study is to analyze the effect of product quality on repurchase intention with consumer satisfaction as an intervening variable for Teh 2 Tang products at PT Perkebunan Teh Assam Jayamengara Indah Sukabumi. The research method employed a quantitative approach, with data collection techniques consisting of questionnaire distribution and field observations. The research sample comprised 100 respondents, determined using the Lemeshow formula. Data analysis was conducted using path analysis to examine both direct and indirect effects among variables. The results indicate that product quality has a positive and significant effect on consumer satisfaction, and consumer satisfaction has a positive and significant effect on repurchase intention. In addition, product quality also has a significant direct effect on repurchase intention. The mediation test using the Sobel method confirms that consumer satisfaction acts as a mediating variable in the relationship between product quality and repurchase intention. These findings suggest that improving product quality is an effective strategy to enhance consumer satisfaction and stimulate repurchase intention, and can therefore serve as a basis for companies in formulating marketing strategies and product development.